The Post-Exercise Window of Susceptibility to Infection: A Literature Review (Bangladesh Journal of Medical Science, 2026)
Objective It is well-established that physical activity offers numerous health benefits; however, it should be performed with appropriate intensity and frequency. This literature review aims to explore the impact of irregular and intense exercise on immune function, with particular emphasis on the “post-exercise window of susceptibility” to infections. Materials and Methods Relevant articles were identified through a targeted search of the PubMed database, focusing on studies examining the effects of exercise on immune function. Selection was based on relevance to the topic and aimed to provide a broad overview of current perspectives. Discussion The current literature indicates that intense physical exertion is associated with exercise-induced muscle damage, inflammation, tissue hypoxia, and hormonal imbalances, all of which appear to contribute to a temporary suppression of immune function. This immune suppression is often manifested by an elevated incidence of upper respiratory tract infections. Furthermore, the literature highlights the protective role of regular, moderate physical activity in promoting long-term immune resilience and reducing the risk of infection. By comparing the short-term immune challenges induced by intense effort with the long-term benefits of consistent training, this review provides a balanced understanding of how exercise influences immune health. Conclusion Structured and sustainable physical activity practices are essential for optimizing immune function while avoiding the temporary immune suppression associated with irregular and excessive exerciseBJMS, Vol. 25 No. 02 April’26 Page: 413-422